2013
DOI: 10.11114/ijsss.v1i2.130
|View full text |Cite
|
Sign up to set email alerts
|

How Social Workers Portray Children’s Perceptions When Constructing Their Identities

Abstract: Constructions of institutional identities are necessary when assessing children's needs and making intervention decisions. To be able to make holistic descriptions of children's identities, social workers have to listen to children's perceptions of themselves and their surroundings. In this study we explore how social workers construct children's identities when portraying the children's perceptions in social investigations conducted according to the BBIC model when concerns have been expressed about the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Although this research has helped to build an awareness of children’s needs, and attempted to articulate the different ways that they may encounter domestic violence, the fact remains that adults (such as parents or professionals) are often unable to accurately represent children’s views and how they experience violence (Edleson, 1999; Øverlien & Holt, 2018). For example, parents or professionals are often not privy to, or able to provide an accurate description of, children’s felt needs and the array of concerns or issues they many have (Hultman & Cederborg, 2013; Moore, McArthur, & Noble-Carr, 2011; Winter, 2010). As a result, research has found that parents or professionals may not be aware of, or may severely underestimate, children’s exposure to, or impact of, violence (Edleson, 1999; Moore et al, 2011).…”
mentioning
confidence: 99%
“…Although this research has helped to build an awareness of children’s needs, and attempted to articulate the different ways that they may encounter domestic violence, the fact remains that adults (such as parents or professionals) are often unable to accurately represent children’s views and how they experience violence (Edleson, 1999; Øverlien & Holt, 2018). For example, parents or professionals are often not privy to, or able to provide an accurate description of, children’s felt needs and the array of concerns or issues they many have (Hultman & Cederborg, 2013; Moore, McArthur, & Noble-Carr, 2011; Winter, 2010). As a result, research has found that parents or professionals may not be aware of, or may severely underestimate, children’s exposure to, or impact of, violence (Edleson, 1999; Moore et al, 2011).…”
mentioning
confidence: 99%
“…I de fall barns situation beskrivs är det därmed ändå främst vuxnas perspektiv på barn som synliggörs. Likaså när barns röster lyfts fram kan det saknas detaljer om deras åsikter, känslor samt önskemål inför framtiden (Hultman och Cederborg 2013). Tidigare forskning visar alltså på variationer när det gäller hur barns röster och erfarenheter dokumenteras i beslutsunderlag.…”
Section: Hantering Av Barns Rätt Till Delaktighet Inom Den Sociala Baunclassified
“…As a directive of this act, the Strategy of Children and Families 2012–2020 () calls for the Swedish assessment framework (Children's Needs in Focus, BBIC – Barns behov i centrum; Socialstyrelsen ) adapted from the ‘Framework for Assessment of Children in Need’ used in England and Wales (Léveillé & Chamberland ; Matscheck & Eklundh ) and based primarily on the previously described UK model (Department of Health ) as the model for Estonia to adapt and implement. The purpose of this model is to strengthen the participation and influence of children, improve co‐operation with the child's parents and extended family and create a system and structure in assessments that underscore the importance of a holistic view of children's development (Hultman & Cederborg ). An investigation of the BBIC model since its adaptation in Sweden shows improved identification of the child's needs in assessments and improvement in building the parents' capacity to meet the child's needs (Matscheck & Eklundh ), and thus, the Estonian Ministry of Social Affairs believes the model is appropriate and shows promise for improving child protection in this country.…”
Section: Introductionmentioning
confidence: 99%